Analisis Kemitraan Dalam Pengelolaan Desa Wisata Kandri Kecamatan Gunungpati Kota Semarang - isnaningtyas, yuliana; ., fitriyah; Marlina, Neny (Journal of Politic and Government Studies, 2017)
Kandri, in Gunungpati subdistrict, is one of the the three village, that was decided as the tour villages, as stated in the decree of Semarang Mayor in 2012. The establishment of the Kandri tour village is aimed to improve the potency of people in Kandri to create the economic independence through tourism sector. This research is aimed to analyze the parthnership in the management of the Kandri tour village in Gunungpati subdistrict.The research method used is a qualitative approach, and the data collection techniques used are documentation, observation and interview. The source of the research are Department of culture and tourism of Semarang, Kandri village, Pandanaran and Sukomakmur tourism awareness group and people in Kandri.The result of the research shows that the Pandanaran tourism awareness group is the one which has responsibility of the managemanet of the tour village. It is the actor which has the center role in creating the improvement of the Kandri tour village. All the involved elements have done their duty and function well so that the people gain the benefit directly and indirectly. The partnership in Kandri tour village is a psudeo parthnership that is appropriate to the condition in the village. Yet, the parthnership is usual and not sustainable. Most of the partnership is done through CSR given by the private institution to the people in Kandri through group of torism awareness. It also involves the government, acadmy and society.Keywords : Tour village, management, parthnership